Silence in the shadows - Coates, Darcy (Coates, Darcy. Black winter, 2020)
"The world continues to change. Each passing day twists it further, and pushes the surviving humans closer to the brink of extinction. But, for the first time, there is hope. Clare and Dorran set their sights back on Winterbourne Hall. It's a daunting journey, but vital. Humanity needs more refuges-safe areas where food can be grown without attracting the attention of the hollow ones. Winterbourne promises to provide that. But their home is no longer a sanctuary ... it has become a trap. By the time they realize just how dangerous it is, the door has slammed closed behind them ... and their fight for survival is far from over."--Provided by publisher.